The Influence of Financial Literacy and Self Control on Women's Personal Financial Management in Konawe District, Southeast Sulawesi Province - Nunsyah, Wa Ode Febry Nur Aisyah; Hidayat, Lusiana Syawalina; Albart, Nicko (Dinasti Publisher, 2024)
The purpose of this study was to determine the influence of financial literacy and self-control of women on their personal financial management. The study was conducted on women in Konawe Regency, Southeast Sulawesi Province. The type of data used in this study is quantitative data. The data source comes from secondary data. The population used in this study were women in Konawe Regency with various different backgrounds. The sampling method used Random Sampling. With a sample size of 100 women. The test results stated that the financial literacy variable had a positive and significant effect on women's financial management and the self-control variable had a significant positive effect on women's financial management.